STUDENTS’ PERCEPTION OF ASYNCHRONOUS IN ENGLISH LEARNING DURING COVID-19 PANDEMIC - Ivan Achmad Nurcholis; Washlurachim Safitri; Riska Rahma Putri (Teaching English and Language Learning English Journal, 2021)
This research aimed to describe how the students’ perception of asynchronous in English learning during covid-19 pandemic in English study program in Muhammadiyah University of Bengkulu. This study used quantitative descriptive research. The subject of the research was the students who followed the Subject of Speaking for Debate of English Education Program of Muhammadiyah University of Bengkulu. The instrument of this research was using the questionnaire. The result shows that the students’ perception of asynchronous learning helped the researchers to develop understanding to present the data to support the problem solving learning activities. During the covid-19 pandemic, asynchronous learning is not effective to be used because the teaching method, media and learning activities were consider inefficient. There are many problems when the conducting the online learning process. In asynchronous learning system, the experiences were a lot of constraints such as the teacher should be able to teach by the distances that must be used the technology. The teacher also must be ready to design learning models and teaching materials and the media. In the other hand, it is hoped that asynchronous learning can be applied in this pandemic era. Keywords: Students’ Perception, Asynchronous Learning, Pandemic Era.